REHABILITACJAInfluence of selected after-surgery factors on physical activity after coronary artery bypass grafting - Storch-Uczciwek, Agnieszka (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Aim: Evaluation of physical activity and the influence of selected after-surgery factors on regular physical activity after coronary artery bypass grafting. Material and Methods: The examination group included 120 men aged 40 to 75, who had been diagnosed with ischemic heart disease. All patients have undergone coronary artery by-pass grafting with the use of extracorporeal circulation. The level of physical activity, both leisure time-related and household-related were evaluated with the use of Paffenbarger questionnaire. The examination was carried out twice: I – during hospitalization due to CABG, one day before operation, II – after the period of 12 months after the procedure. According to the instructions of the applied questionnaire the total weekly energy expenditure [kcal/week] was calculated and a division of effort was made: low, moderate, and high. Results and Conclusions: The acquired data allowed for description of real level and range of weekly energy expenditure in studied subjects expressed in calories/week. The level, measured both before and after the revascularization surgery, did not exceed the value of 2000 kcal/week. Next the analysis of the influence of select factors on systematic physical activity after coronary artery bypass grafting showed that the participation in outpatient (phase II) cardiac rehabilitation was the strongest factor which made studied subjects undertake physical activity within 12 months after the surgical treatment of ischemic heart disease. Fatigue and weakness, chest pains and lower extremity symptoms related to the surgical treatment resulted also in decrease in the total energy expenditure connected with physical activity in those patients.